2019
DOI: 10.1177/2331216519846232
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Interactions in Stereo Sound Localization for Individuals With Unilateral Hearing Loss

Abstract: This study investigated the effects of unilateral hearing loss (UHL), of either conductive or sensorineural origin, on stereo sound localization and related visual bias in listeners with normal hearing, short-term (acute) UHL, and chronic UHL. Time-delay-based stereophony was used to isolate interaural-time-difference cues for sound source localization in free field. Listeners with acute moderate (<40 dB for tens of minutes) and chronic severe (>50 dB for more than 10 years) UHL showed poor localization and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…A primary alternative to distorted or unavailable ITDs and ILDs is monaural cues from the intact ear (Agterberg et al, 2014;Irving and Moore, 2011;Kumpik et al, 2010;Shub et al, 2008;Slattery and Middlebrooks, 1994;Van Opstal, 2004, 2007). More recently, Venskytis et al (2019) investigated how the duration and severity of unilateral hearing loss (UHL) affect auditory localization. They compared the performance of four hearing groups-normal hearing, acute UHL (minutes, by ear-plugging), chronic moderate UHL, and chronic severe UHL (more than 10 years, no hearing aid experience) using time-delay-based stereophony.…”
Section: Learning and Plasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…A primary alternative to distorted or unavailable ITDs and ILDs is monaural cues from the intact ear (Agterberg et al, 2014;Irving and Moore, 2011;Kumpik et al, 2010;Shub et al, 2008;Slattery and Middlebrooks, 1994;Van Opstal, 2004, 2007). More recently, Venskytis et al (2019) investigated how the duration and severity of unilateral hearing loss (UHL) affect auditory localization. They compared the performance of four hearing groups-normal hearing, acute UHL (minutes, by ear-plugging), chronic moderate UHL, and chronic severe UHL (more than 10 years, no hearing aid experience) using time-delay-based stereophony.…”
Section: Learning and Plasticitymentioning
confidence: 99%
“…They compared the performance of four hearing groups-normal hearing, acute UHL (minutes, by ear-plugging), chronic moderate UHL, and chronic severe UHL (more than 10 years, no hearing aid experience) using time-delay-based stereophony. This stereophony technique allowed Venskytis et al (2019) to manipulate ITD cues while keeping ILDs near zero and the monaural spectral information relatively unchanged so that ITDs were essentially isolated as the cue for sound source localization in the horizontal plane. They found that the chronic, moderate UHL group performed near normal while the severe and acute groups could not do the task.…”
Section: Learning and Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…These findings clearly argue for multisensory stimulation to help recalibration in acute AHL and—in line with our suggestion—make a case for necessity of a visual component to over‐rely on to help steer auditory localization in the right direction. Concordantly, Venskytis et al (2019) found that people overweighed visual information, especially on the impaired side, in acute (plugged for tens of minutes) and severe chronic (>12 years) unilateral hearing loss, implying a compensatory role for vision to restore perceptual asymmetries even after long‐term hearing loss. All in all, we suggest that over‐relying on visual input may facilitate recalibration of auditory signals in the long run.…”
Section: Discussionmentioning
confidence: 87%
“…Although much has been learned about how our senses collaborate to facilitate perception in various circumstances and in various disorders, knowledge about the impact of common auditory impairments on MSI is currently scarce. Worldwide, about 466 million people suffer from hearing loss (WHO, 2020), but the impact of different types of hearing loss on how the senses work together is rarely investigated (though see Gieseler et al, 2018; Venskytis et al, 2019). Common subtypes of hearing loss are dissociable by their aetiology: sensorineural hearing loss occurs after damage to the inner ear (e.g., hair cells or auditory nerve), whereas conductive hearing loss is a consequence of damage to the middle or outer ear (e.g., perforated eardrum, otosclerosis, malformations or inflammations).…”
Section: Introductionmentioning
confidence: 99%